Multiferroicity in a quasi-one-dimensional magnet MnSb2Se4. (January 2022) - Kumar, Rahul; Sundaresan, A.
Highlights: Spin-driven multiferroicity was observed at antiferromagnetic transition temperature of MnSb2 Se4 . New ferroelectric transition observed under higher magnetic fields and clearly distinguishable at 9 T. Quasi-one-dimensional magnetic behavior of MnSb2 Se4 was realised along b -axis. Abstract: We report a comprehensive study of the structural, magnetic, and multiferroic properties of a quasi-one-dimensional magnet, MnSb2 Se4, crystallizing in a centrosymmetric monoclinic structure. Magnetic and heat capacity measurements revealed that this compound undergoes a long-range antiferromagnetic ordering at T N  = 22.5 K. A dielectric anomaly appeared at the T N in the absence of a magnetic field, and, an applied magnetic field of 9 T induced another dielectric anomaly just below the T N. Furthermore, the pyroelectric and DC-bias current measurements confirmed that these anomalies are associated with spontaneous electric polarization, whose magnitude becomes almost double under an applied field of 9 T. These results demonstrated that MnSb2 Se4 is a type-II multiferroic material with strong magnetoelectric coupling. Moreover, a frequency-dependent dielectric anomaly observed at 5 K in the real component of the dielectric permittivity and loss data indicates relaxor behavior. Graphical abstract: Image, graphical abstract